Mobile Telecommunication and Economic Growth: Evidence from ARDL Modeling - Ibrahim Musa; Sule Magaji; Ali Salisu (Research Synergy Foundation, 2023)
This study examines the impact of mobile telephone on economic growth in Nigeria using ARDL (Autoregressive distributed lag) as methodology, with data from 2001-2017. The study reveals that mobile penetration had a positive impact on real GDP per capita. Which means as more people get access to mobile phones, GDP per capita is expected to grow. 10% increase in mobile penetration will lead to a 0.5 % increase in average annual GDP per capita. The study concludes that mobile telephony can aid sustainable economic development when used appropriately, with the full participation of all stakeholders, especially in a country like Nigeria. The intrinsic value of telecommunications lies not in easing communications and information, but in enabling growth and development. The study recommends that Consumer protection policies are needed to protect consumers from unfair calls and mobile data charges will ensure consumer get the value for their money, which will lead to increased consumption and investment in the industry.